Research and teacher education with MTSK in Mato Grosso and Mato Grosso do Sul (Research, Society and Development, 2020)
The aim of this research is to present contributions and impacts in terms of specialized knowledge to teach Mathematics obtained in MTSK-based research and training actions / projects in Mato Grosso and Mato Grosso do Sul. The theoretical framework Mathematics Teacher's Specialized Knowledge - MTSK. The methodology is qualitative and documentary, in the region in question, analyzing the actions of two research / training groups (TSK Group and TeiaMat) to understand the contributions and impact with / on MTSK specialized knowledge. In general, the results show that both groups analyzed develop different projects that promote relevant actions, reflections and perspectives for teacher education in the region.